Creating A Seamless User Experience: The Perceived Value Of Wayfinding In Retail Interior Design - Mosebi, Itumeleng (The IIE, 2022)
The purpose of this research is to explore and describe the impact of the use of wayfinding in retail interior design in regard to the user to create a more seamless experience. This can then help brands to look at creating more conducive retail environments that influence the customers experience. The findings of this study have the ability to expand the knowledge regarding the effects of wayfinding in retail interior design. The use of constructivist paradigm in this study is intended to gain in depth understanding of the customers’ experiences by exploring the impact of using wayfinding in a physical environment. The researcher intends to use qualitative descriptive design as it is known to study human behaviour in everyday or natural setting, and involves continuous interaction with the people being studied in their own language, and on their own understanding. For the purpose of this study the researcher intends to make use 6-10 customers, that include men and women from all ages 19 to 24. The researcher will use a non-probability sampling method, as it does not make us of a random selection of population elements. A purposive sampling will be used, as the researcher wishes to target a younger customer demographic. In this study the data collection method will make use of surveys or questionnaires, that consist of open ended questions. Additionally, a thematic analysis or theming will be the method used to interpret the gathered data.
Keywords: Customer behaviour; Buying patterns; Brand loyalty; Brand awareness